Grain growth in thin nanocrystalline silver films. (15th April 2016) - Sursaeva, V.G.; Gottstein, G.; Shvindlerman, L.S.
Abstract: The results of grain growth experiments in nanocrystalline films deposited on a substrate are discussed in the framework of a theoretical concept in which grain growth is accompanied by vacancy generation to compensate for the released excess volume. It is shown that the predicted "incubation time", which precedes grain growth is also observed in experiment. The measured "incubation time" can be utilized to determine the grain boundary excess free volume. The results compare reasonably well to values obtained in experiments, where the pressure dependence of grain boundary energy was measured. Graphical abstract: